Given that x , y are real numbers such that 5 x + 9 y = 0 , and
x 2 + x y = 1 2 and 2 x y + 3 y 2 + 5 = 0 ,
then what is the value of x + 4 y ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
But you mentioned 5x+9y is not equal to 0. Also from your solution, I fail to understand why x+4y cannot be 0. Just substitute x=4 and y=-1, all conditions are satisfied and 5x+9y is 11 in that case.
Log in to reply
( − 4 , 1 ) → − 1 1 is a solution as well.
Sorry, the question should have read "what is the value of x + 4 y ". I introduced an error when I edited the problem.
the answer is either +11 (x=4, y=-1) or -11 (x=-4, y=1). Both satisfy all the conditions given. none of the given options are correct.
A SIMPLE FACTORING...x^2 + xy - 12 = 0 can easily be factored into (x+6)(x-2), (x-6)(x+2),(x+4)(x-3),(x-4)(x+3), (x-12)(x+1), (x+12)(x-1) to find integer solutions for y. It can quickly be seen that x=-4 and y=1 or x=4 and y=-1 solves the second equation, while the other solutions do not, giving the answer (x+4y) = 0. Might save time on a test, if you assume x and y are integers, or might not. Another quick way to find an integer solution is to use the quadratic formula: (-y +- squareroot(y^2+48))/2. When y=-1, we get (1+7)/2 = 4. So again, x=4, y=-1 and (x+4y)=0.
Letz do it by crunch mathod.....put x=4 & y= -1..... It will satisfy both equation..... Putting the value in the equation... 4+ 4× (-1) = 0
we see that 2xy + 3y^2+5 = 0, the last 2 terms of this problem are positive , so 2xy must be negative to give 0.So, one out of x and y must be positive and the other negative. 12 = 1 12,2 6,3*4.Factoring x^2 + xy = x(x+y) and substituting value and trying for both the equations, we get x = 4,y=-1 .Substituting this in x+4y, we get answer to be 0.
Problem Loading...
Note Loading...
Set Loading...
5 x 2 + 5 x y = 6 0 , 2 4 x y + 3 6 y 2 = − 6 0 Add and factorise to get ( x + 4 y ) ( 5 x + 9 y ) = 0